ISLAMIC CREED PERSPECTIVES ON STUDENTS WEARING NIQAB IN SALAFI-MINDED COLLEGES IN EAST JAVA PROVINCE - Kumaini, Ruston; Saiful Anwar; Muhammd Tsalis Ramdlani (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
The niqab or veil, as a manifestation of religious identity, has been a subject of societal discussion, with perspectives often centered on issues of autonomy, cultural diversity, and perception. This study aims to reveal the Islamic creed perspectives of wearing-niqab students in an academic environment and examine the understanding of wearing-niqab students’ attitudes toward themselves, their experiences wearing the niqab, interactions with the campus environment, and their perceptions of how other members of the academic community perceive them. The researchers surveyed a sample of 177 female students from 2 colleges affiliated with the Salafi Manhaj in East Java Province, namely STDI Imam Syafi'i Jember and STAI Ali bin Abi Thalib Surabaya. The survey used Likert-type items. The findings of this research are: 1) 65% of wearing-niqab students choose to wear the niqab based on their Islamic creed and the majority (84.2%) of respondents believe that the law of wearing niqab is sunnah, and it’s believed as a form of worship and obedience to Allah and His Messenger. 2) the majority of the respondents (94.9%) felt very confident, while only a small proportion of respondents (5.1%) felt very insecure, and all of the respondents see themselves as part of Indonesian society. 3) most of the respondents (82.5%) have been wearing the niqab consistently since they were teenagers, all respondents never get bullied while on campus and just a small proportion of them (10.8%) often get bullying off campus and the majority of them are open minded people and wants to interact with society.